Maritime delimitation of the territorial sea in accordance with the 1982 United Nations Convention on the Law of the Sea - Halaimia, Meriem (Journal of Human Sciences, 2023)
This study addresses the method of delimitation of the territorial sea, any rule adopted to determine the baselines from which the extent of the territorial sea and other maritime areas is measured, as well as the status of the territorial sea located in one State, or the situation of opposite or adjacent States, under the provisions of the 1982 Convention on the Law of the Sea, having established its own legal nature.